Unpopular privacy what must we hide? - Allen, Anita L., 1953- (New York ; Oxford : Oxford University Press, 2011)
Can the government stick us with privacy we don't want? It can it does, and according to this author, may need to do more of it. Privacy is a foundational good, she argues, a necessary tool in the liberty-lover's kit for a successful life.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Privacy, Right of -- United States; Women's rights -- United States